2015
DOI: 10.1017/s2045796015000359
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and discrimination related to mental illness in low- and middle-income countries

Abstract: Generating information about effective interventions to reduce stigma and discrimination in LAMICs is now an important mental health priority worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
129
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(138 citation statements)
references
References 55 publications
8
129
0
1
Order By: Relevance
“…Overall, stigma against help-seeking was low and reflects trends obtained from other research from LMIC (Semrau et al 2015). A third of the population had a neighbour or family member with mental illness and that may have acted as an interpersonal contact resulting in reduced stigma.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Overall, stigma against help-seeking was low and reflects trends obtained from other research from LMIC (Semrau et al 2015). A third of the population had a neighbour or family member with mental illness and that may have acted as an interpersonal contact resulting in reduced stigma.…”
Section: Discussionsupporting
confidence: 84%
“…Mental health attitudes has been found to improve following anti-stigma and mental health awareness campaigns, but not knowledge, even in high-income countries, and no conclusive data are available for behaviour change. Data from LMIC are almost negligible and what little exists is inconclusive about the effectiveness of the interventions or the overall outcomes (Semrau et al 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the intervention period people’s attitudes and behaviors appeared to improve but not their scores on knowledge, and this is similar to other studies [17]. Stigma related to help–seeking was low and is similar to earlier research from LMIC [43]. …”
Section: Discussionsupporting
confidence: 88%
“…A recent review observed a treatment gap of more than 90% for CMDs in India and China, two relatively well-resourced middle-income countries (Chisholm et al 2016, Patel et al 2016b). There are many reasons for the poor coverage of psychological treatment including a reliance on a limited number of specialists to provide or supervise treatments, as well as to train therapists (Kohrt et al 2015); the use of highly specific disorder-based treatment packages (England et al 2015, Kazdin 2016, Murray et al 2014, Weisz et al 2012); and the stigma of seeking help for CMDs and other mental illnesses (Semrau et al 2015). …”
Section: Introductionmentioning
confidence: 99%